Constraints and opportunities for tree diversity management along the forest transition curve to achieve multifunctional agriculture - Ordoñez, J.C.; Luedeling, Eike; Kindt, Roeland; Tata HL; Harja D; Jamnadass, Ramni H.; Noordwijk, Meine van (Elsevier, 2014)
On-farm tree diversity patterns result from a social-ecological process shaped by different actors. Farmer preferences, tree-site matching, seed dispersal, tree domestication and delivery via nurseries all play important roles in forming these patterns. As part of a wider interest in tree cover transition curves that link agroforestation stages of landscapes to a preceding deforestation process, we here focus on ‘tree diversity transition curves’ i. as a conceptual framework to understand current processes and how shifts in drivers affect tree diversity and ii. to help identify constraints and opportunities for interventions. We provide some examples of current research efforts and make suggestions for databases and analyzes that are required to improve our understanding of tree diversity transitions. We explore drivers, consequences and entry points for tree diversity management to achieve multifunctional agriculture.